Elementa as a Subject of Discussion with Heresies in Philastrius of Brescia’s "Diversarum hereseon liber" - Szram, Mariusz (Vox Patrum, 2024)
The aim of the research is to determine the semantic field of the term elementa in one of the oldest Latin catalogs of heresies – Philastrius’ Diversarum hereseon liber (after 381), and to display the philosophical and theological issues linked with this concept, discussed about in early Christianity, which was reflected in the work of the Bishop of Brescia. Analysis of the source text leads to the following conclusions: 1) the term elementum occurs in the treatise in the plural in a cosmological context, both in the general sense of the components of the world and in the specific sense of the four elements; 2) the views of heretics are dominated by meanings inspired by various currents of ancient philosophy, while for Philastrius, the main determinant of the content of the term elementa is the biblical message; 3) the main topics addressed by the term oscillate around protology and eschatology, and are triggered by ideas that Philastrius considers heretical, such as views that regard the elements as rational entities, or beliefs in the immutability and eternal persistence of the elements or in their ultimate disappearance; 4) among the cosmological heresies criticized by Philastrius, Gnostic movements dominate, as well as unnamed groups that give the divine worship to particular elements; 5) the position of the Bishop of Brescia, which is opposed to these views, is characterized by: faithfulness to the descriptions of creation from the Book of Genesis, comprehended literally; the conviction that the elements pertain exclusively to material reality and have a connection with the created world; an approach to the fate of the elements after the end of the present world that is devoid of spiritualistic extreme, assuming their continued existence, but in an altered form.